Closing the Productivity Gap: Improving Worker Productivity Through Public Relative Performance Feedback and Validation of Best Practices - Song, Hummy; Tucker, Anita L.; Murrell, Karen L.; Vinson, David R. (Management science, 2018)
Public relative performance feedback (RPF) on an individual worker’s productivity metrics is used in various organizations with the hopes of improving worker productivity, but its effects are not well understood. We examine whether public RPF could be leveraged to facilitate adoption of best practices in an organization by enabling the validation of best practices shared by identifiable top performers. We use data from two emergency departments, both of which shared best practices for improving productivity and one of which changed from privately to publicly disclosing RPF to physicians. The public disclosure of RPF allowed workers to identify their top-performing coworkers, which in turn enabled the identification and validation of best practices within the work group. We find that the intervention is associated with a 10.9% improvement in physician productivity. We also find evidence for a significant reduction in variation in productivity across providers, which stems from bottom-ranked workers exhibiting differentially large improvements in productivity. These effects hold without sacrificing system-level performance, service quality, or worker attrition. Our results suggest that public disclosure of RPF, along with the validation of the best practices being shared, can improve worker productivity. The online supplement is available at https://doi.org/10.1287/mnsc.2017.2745 . This paper was accepted by Serguei Netessine, operations management.